2017
DOI: 10.4254/wjh.v9.i20.896
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections post-living-donor liver transplantation in Egyptian hepatitis C virus-cirrhotic patients: A single-center study

Abstract: AIMTo determine risk factors, causative organisms and antimicrobial resistance of bacterial infections following living-donor liver transplantation (LDLT) in cirrhotic patients.METHODSThis prospective study included 45 patients with hepatitis C virus-related end-stage liver disease who underwent LDLT at Ain Shams Center for Organ Transplant, Cairo, Egypt from January 2014 to November 2015. Patients were followed-up for the first 3 mo after LDLT for detection of bacterial infections. All patients were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…In our study, 58.3% of infection attacks were sourced by the hepatobiliary system (cholangitis, intraabdominal abscess, infected biloma, and pancreatitis). Nosocomial MDR gram‐negative microorganisms predominate an infections originating from the hepatobiliary system 26 . Particularly high mortality rates, in the range of ~35%‐70%, are reported for patients developing infections with MDR microorganisms, such as ESBL‐producing or carbapenem‐resistant Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 58.3% of infection attacks were sourced by the hepatobiliary system (cholangitis, intraabdominal abscess, infected biloma, and pancreatitis). Nosocomial MDR gram‐negative microorganisms predominate an infections originating from the hepatobiliary system 26 . Particularly high mortality rates, in the range of ~35%‐70%, are reported for patients developing infections with MDR microorganisms, such as ESBL‐producing or carbapenem‐resistant Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were probed with fluorescent solution SA-FLOUS (Origin Biosciences Inc., Nanjing, China) after centrifugation. To assess cell apoptosis, the fluorescence was detected using a 620-nm bandpass filter for PI and a 525-nm bandpass filter for FITC at 488-nm excitation wavelength, respectively [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intra-abdominal infections were the most frequently encountered infection, of which Enterococcus species were the leading pathogens. Montasser et al [67] in the prospective study included 45 patients who underwent LDLT at Ain Shams Center for Organ Transplant, 33 patients (73.3%) were suffered from bacterial infections. The study done in National liver institute Menoufya in 2015 showed that the HCV recurrence was 19.2% [68].…”
Section: Pre-transplant Detection Of Active Bacterial Infectionmentioning
confidence: 99%